2010
DOI: 10.3390/v2081577
|View full text |Cite
|
Sign up to set email alerts
|

A VSV-G Pseudotyped Last Generation Lentiviral Vector Mediates High Level and Persistent Gene Transfer in Models of Airway Epithelium In Vitro and In Vivo

Abstract: The aim of this work was to evaluate the efficiency and duration of gene expression mediated by a VSV-G pseudotyped last generation lentiviral (LV) vector. We studied LV efficiency in ex-vivo models of respiratory epithelial cells, obtained from bronchial biopsies and nasal polyps, by GFP epifluorescence and cytofluorimetry. In vivo efficiency and persistence of gene expression was investigated by GFP immunohistochemistry and luciferase activity in lung cryosections and homogenates, respectively, upon intranas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…Large volumes of LV vector (100 µl) administered to the nasal airways are able to effectively transduce both nasal and lung airways . Furthermore, LPC pre‐treatment may not be required for efficient lung transduction with VSV‐G pseudotyped LV vectors . Therefore, the findings of the present study suggest that LPC pre‐treatment, as used in nasal airways, may not be essential for progenitor cell access in the lung.…”
Section: Discussionmentioning
confidence: 79%
“…Large volumes of LV vector (100 µl) administered to the nasal airways are able to effectively transduce both nasal and lung airways . Furthermore, LPC pre‐treatment may not be required for efficient lung transduction with VSV‐G pseudotyped LV vectors . Therefore, the findings of the present study suggest that LPC pre‐treatment, as used in nasal airways, may not be essential for progenitor cell access in the lung.…”
Section: Discussionmentioning
confidence: 79%
“…In vivo studies in mice have shown that the VSVg is unable to efficiently transduce the lung and relies on chelating and surfactant agents for its entry into respiratory epithelial cells. 9,12,13,61 Indeed, we also observed that VSVg LV transduced murine lung slices poorly, despite transducing ovine lung tissue slices similarly to DGP Jenv and the DGP Jenv mutant LVs. Conversely, the EBOV GP-pseudotyped LV has shown promising results in mice.…”
Section: Discussionmentioning
confidence: 51%
“…10,11 Thus, chelating and surfactant agents are being developed and utilized to transiently disrupt the tight junctions in the lung epithelium and facilitate VSVg-LV entry. 12,13 Though this approach may be suitable for some genetic diseases of the lung, the use of chelators might not be appropriate for others, such as Cystic Fibrosis (CF). 7,14 Cumulative disruption of tight junctions could lead to inflammation or bacterial translocation, thereby enhancing the pathology of CF.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have capitalized on this observed long‐term efficacy of the VSV‐G pseudotyped vector, and have attempted to transduce the CFTR gene as a means to specifically treat CF (Goldman et al, ; Copreni et al, ). In one study, the authors utilized a human bronchial xenograft model, and reported a stable CFTR transgene expression that was capable of functionally correcting the CF defect in CF knockout mice after the graft matured (Goldman et al, ).…”
Section: Lentiviral Vectors In Gene Therapymentioning
confidence: 99%